EVALUATION OF APHRODISIAC ACTIVITY OF ETHYL ACETATE FRACTION OF CLOVE LEAVES (Syzygium aromaticum L.) IN MALE WHITE RATS (Rattus norvegicus) - Muthmainah Tuldjanah; Rezky Yanuarty; Agung; Ayu Wulandari (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Clove leaves contain antioxidant compounds such as saponins, flavonoids, tannins, sterols, and essential oils. Among those chemical constituents, eugenol, eugenol acetate, caryophyllene, and sesquiterpenes were believed to have aphrodisiac activity. This study aims to investigate the potential aphrodisiac effects of the ethyl acetate fraction of clove leaves (Syzygium aromaticum L) administered at a dose of 250 mg/kg BW. The research employed an experimental method with a modified post-test randomized controlled group design and utilized a total of 45 white rats, consisting of 15 males and 30 females, divided into three treatment groups in a 1:2 ratio. Each group consisted of 5 male rats and 10 female rats. The three groups included the healthy control group (Na-CMC 0.5%), the positive control group (treated with X-Gra 52.5 mg/kg body weight) and the treatment group receiving clove leaf extract samples at a dosage of 250 mg/kg BW. The results indicate that the ethyl acetate fraction of clove leaves contains steroids and alkaloids with mount latency (ML), intromission latency (IL) ejaculation latency (EL), mount frequency (MF), intromission frequency (IF) and ejaculation frequency (EF) of 11.40 s, 15.80 s, 6.228 s, 23.60, 14.60, and 1.60 s, respectively. Based on these findings, it can be concluded that it has the potential to be used as an aphrodisiac agent. Keywords: Aphrodisiac, Syzygium Aromaticum L., ethyl acetate fraction, clove leaves, ejaculation frequency